CONCORDANCE BETWEEN THE DIAGNOSIS OF HYPERTENSION BY OFFICE BLOOD PRESSURE AND HOME BLOOD PRESSURE MONITORING IN A FAMILY HEALTH CARE UNIT- LAPARC COHORT STUDY. (April 2021) - Botelho, Bruna Gopp; Barbalho, Daniella Gomes; Louzada, Vinicius Leiria Teixeira; Azevedo, Rafael Bellotti; Sampaio, Fernando Bizzo; Antequera, Lucas Alves; Diniz, Pedro Henrique Pimenta; Marinho, Beatriz Deberaldini; Rocha, Débora De Castro; Ferreira, Leonardo Villa Leão; Velasco, Pedro Julio Pacheco; Araujo, Humberto Montilho; et al.
Abstract : Objective: To evaluate concordance between diagnosis of hypertension by Office Blood Pressure (OBP) and Home Blood Pressure Monitoring (HBPM) in a young adult population. Design and method: A cross-sectional population study enrolled adults between 20 and 50 years registered in a primary healthcare unit in the city of Rio de Janeiro, Brazil. Socio-demographic and anthropometric characteristics were registered at the entrance of the study. Also, the presence of CV risk factors was evaluated. OBP was determined by calculating the mean value of 2 consecutive measurements (Omron-705CP) while the HBPM followed a 7-day protocol with 2 measurements in the morning and 2 in the evening (28 measurements). Measurements of the first day were discarded and the average of the other 6 days was calculated. It was considered normal a Home BP < 135 x 85 mmHg and OBP < 140 x 90 mmHg. Patients were classified into 4 groups: normotension (controlled OBP and HBPM); white coat hypertension (uncontrolled OBP and controlled HBPM); masked hypertension (controlled OBP and uncontrolled HBPM) and sustained hypertension (uncontrolled OBP and HBPM). Results: A total of 462 individuals were evaluated [37.7% males with mean age 37.4 ± 8.8 years]. Sedentary lifestyle (43%), dyslipidemia (38%) and obesity (28%) were the main CV risk factors. By OBP, the prevalence of hypertension was 13.4% while by HBPM was 18.6%. Kappa coefficient demonstrated a low concordance between the two diagnostic methods (kappa = 0.472). After HBPM, 68 individuals (16.9%) changed the diagnosis, being 21 (5.6%) with white coat hypertension and 45 (11.3%) with masked hypertension. The variables that were independently associated with hypertension diagnosed by OBP were male gender (OR 1.83, CI95%, 1.01–3.33, p = 0.04) and increased neck circumference (OR 3.77, CI95%:1.59–8.93, p = 0.003). Hypertension diagnosed by HBPM was associated with obesity (OR 2.18, CI95%, 1.27–3.76, p = 0.005) and increased neck circumference (OR 2.37, CI95%, 1.05–5.33, p = 0.04). Conclusions: Concordance between office BP and HBPM was low in this young adult population. Thus, If the diagnosis was based only in the office BP values, 17.5% of the subjects would have an erroneous diagnosis of hypertension.